Significantly Altered Serum Levels of NAD, AGE, RAGE, CRP, and Elastin as Potential Biomarkers of Psoriasis and Aging-A Case-Control Study - Karas, Adam; Holmannova, Drahomira; Borsky, Pavel; Fiala, Zdenek; Andrys, Ctirad; Hamakova, Kvetoslava; Svadlakova, Tereza; Palicka, Vladimir; Krejsek, Jan; Rehacek, Vit; Esterkova, Monika; Kovarikova, Helena; et al. (Biomedicines, 2022)
BACKGROUND: This study aims to investigate potential markers of psoriasis and aging, and to elucidate possible connections between these two processes. METHODS: The serum samples of 60 psoriatic patients and 100 controls were analysed, and the levels of four selected parameters (AGEs, RAGE, NAD, and elastin) were determined using commercial ELISA kits. Serum C-reactive protein was assayed using an immune-nephelometry method. FINDINGS: Among the patients, the levels of CRP, AGEs, and RAGE were all increased, while the levels of NAD were reduced when compared to the control group. A negative correlation between the levels of AGEs and NAD was found. A negative correlation between age and the NAD levels among the control group was observed, however among the patients the relationship was diminished. While there was no difference in the levels of native elastin between the patients and the controls, a positive correlation between the levels of native elastin and age and a negative correlation between the levels of native elastin and the severity of psoriasis were found. CONCLUSIONS: The results of our study support the notion of psoriasis and possibly other immune-mediated diseases accelerating the aging process through sustained systemic damage. The serum levels of CRP, NAD, AGEs, and RAGE appear to be promising potential biomarkers of psoriasis. The decrease in the serum levels of NAD is associated with (pro)inflammatory states. Our analysis indicates that the levels of native elastin might strongly reflect both the severity of psoriasis and the aging process.
Keywords: NAD; elastin; psoriasis; CRP; AGEs; RAGE; biomarkers; inflammaging